Zoroastrismo da Pérsia e catolicismo romano: um estudo comparado entre concepções escatológicas - Henriques, Ana Cândida Vieira (2019)
Our research brings to the clarity of contemporary scholarship an eschatological question situated in the origins of two Salvationist religions: Zoroastrianism of Persia and Roman Catholicism. In general, the eschatologies of religions present themselves as a framework of postmortem conceptions of an individual and collective character that aim to give effective answers to the existential human problem. In these terms, these two religions present individual eschatologies which denote common elements, at first glance, as regards the doctrines of the resurrection of bodies and the immortality of the soul, extending to the notions of judgment, paradise, hell and the intermediate state. In this sense, our problem focuses on the possibility of influences that Zoroastrianism has exerted on Catholicism, in the elaboration of eschatological conceptions of the latter. Taking into account the great temporal gap between the foundational milestone of both religions - at least six centuries, attested by Iranian scholars - we intend to investigate a possible eschatological assimilation by Roman Catholicism. As a theoretical reference, we will rely on the studies of great Iranians, such as Duchesne-Guillemin, Mary Boyce and Gerard Gnoli, as well as scholars of the religions, such as Mircea Eliade, Geo Widengren, John Dominic Crossan, among others. We will also make use of official documents and sacred scriptures of both religions, such as the Gáthas and other books of the Zoroastrian Avesta, as well as the Catechism of the Catholic Church and some conciliar and apostolic constitutions. As for the method adopted to reach our goal, we will make use of the comparative study between the two eschatologies.